2019
DOI: 10.32890/mjli2019.16.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Practices in the Acquisition of English by Asian Immigrant English Language Learners

Abstract: Purpose - The increase in the enrolments of immigrant children in New Zealand seems to have posed great challenges to early childhood education services when it comes to developing the children’s English language acquisition. This qualitative case study explored how New Zealand early childhood teachers develop the English language acquisition of Asian immigrant English language learners (ELLs). The theoretical framework of this research drew on a range of sociocultural perspectives, including sociocultural ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
(7 reference statements)
0
0
0
1
Order By: Relevance
“…Socio-cultural is the eighth or final issue identified, with six articles discussing it (Al-Darwish, 2012;Goh, 2019;Hegde et al, 2018;Leung et al, 2013;Mustafa et al, 2019;Nafissi & Shafiee, 2020). In a study by Al-Darwish (2012), young children's motivation to learn English is critical, and it may occur as some parents refuse their children to learn any foreign language at all.…”
Section: Pollard-durodola Et Al (2012)mentioning
confidence: 99%
See 2 more Smart Citations
“…Socio-cultural is the eighth or final issue identified, with six articles discussing it (Al-Darwish, 2012;Goh, 2019;Hegde et al, 2018;Leung et al, 2013;Mustafa et al, 2019;Nafissi & Shafiee, 2020). In a study by Al-Darwish (2012), young children's motivation to learn English is critical, and it may occur as some parents refuse their children to learn any foreign language at all.…”
Section: Pollard-durodola Et Al (2012)mentioning
confidence: 99%
“…There is an argument from preschool teachers that ELT affects young children's ELL when their mother tongue language and socio-cultural identity have not been shaped (Nafissi & Shafiee, 2020). While preschool teachers provide an 'alteration' of approaches in ELT, there are circumstances where the approaches are incongruent with the ELLs' culture (Mustafa et al, 2019). In relation to this, Leung et al (2013) indicated that there is a strong demand by parents who prefer native-English language teachers to teach than local teachers.…”
Section: Pollard-durodola Et Al (2012)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ini kerana kemahiran literasi awal merupakan peramal bagi penguasaan membaca dan menulis kanak-kanak pada masa akan datang (Machado, 2016;Ozernov-Palchik et al, 2016). Kemahiran literasi awal juga merupakan aspek penting bagi program pendidikan awal kanak-kanak (PAKK) yang komprehensif dan telah meluas sehingga ke taska (Mazlina et al, 2018(Mazlina et al, , 2019. Kadang kala, maklumat berkaitan pencapaian kemahiran literasi awal kanak-kanak ditafsirkan sebagai gambaran bagi semua aspek pengajaran dalam sesebuah program PAKK (Strickland & Ayers, 2007).…”
Section: Pengenalanunclassified
“…12 Bil. 2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) implement categorization, the tendency to draw conclusions and the tendency to ensure the details of the description. Kamarul Azmi Jasmi, Ab.…”
Section: A Introductionmentioning
confidence: 99%